Protective effect of melatonin on alleviating early oxidative stress induced by DOX in mice spermatogenesis and sperm quality maintaining - Teng Zi; YaNan Liu; YuSheng Zhang; ZeLin Wang; ZhiXin Wang; Song Zhan; Zhu Peng; Ning Li; XueXia Liu; FuJun Liu (BMC, 2022)
Abstract Doxorubicin (DOX) is an effective chemotherapy drug, but its clinical use has adverse effects on male reproduction. However, there are few studies about the specific biological processes related to male reproduction or strategies for improving fertility protection. In this paper, we examined the effects of DOX on spermatogenesis and sperm function, and tested the possible protective role of melatonin (MLT) against DOX's reproductive toxicity. DOX-treated mice showed signs of significantly impaired spermatogenesis, including vacuolated epithelial cells, decreased testis weights, and lowered sperm counts and motility. DOX also reduced germ cell proliferation (PCNA) and meiosis-related proteins (SYCP3), but this effect could be partially improved with MLT administration. HSPA2 expression was maintained, which indicated that although MLT did not improve sperm motility, it did have a significant protective effect on elongated sperm. IVF results showed that MLT could partially promote two-cell and blastocyte development that was restricted by DOX. MLT reversed DOX-driven changes in the testes, including the antioxidant indices of SOD1, CAT and PRDX6, and the apoptotic indices of BAX and Caspase3. These results suggest that MLT effectively prevents DOX-induced early reproductive toxicity, and increase our understanding of the molecular mechanisms underlying DOX's effects on male reproduction and the protective mechanism of MLT.